2021
DOI: 10.1002/jsfa.11298
|View full text |Cite
|
Sign up to set email alerts
|

Barnyard grass [Echinochloa crus‐galli (L.) Beauv] leaves extract against tomato pests

Abstract: BACKGROUND: Tomato is one of the widely cultivated crops worldwide that is affected by several pests, such as fungi (Fusarium oxysoporum, Alternaria solani), bacteria (Pectobacterium carotovorum) and weeds (Cyperus iria L., Amaranthus spinosus).A growing interest has emerged for developing plant-derived pesticidal compounds to counteract these pests. One attractive alternative is to use barnyard grass (Echinochloa crus-galli), known to be widely resistant to synthetic herbicides, as a potential biopesticide co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…First, we created a database of all known and reported compounds found in select plant species that were reported to have cytotoxic activities: Mangifera indica , Artocarpus heterophyllus , Annona muricata , Lansium domesticum , Manilkarazapota , Antidesma bunius . Using a LC-MS/MS metabolomics workflow, it was previously reported that leaf extract fractions from these plant species contained characteristic phytochemicals (phenolics and flavonoids) that exhibited cytotoxic activities. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we created a database of all known and reported compounds found in select plant species that were reported to have cytotoxic activities: Mangifera indica , Artocarpus heterophyllus , Annona muricata , Lansium domesticum , Manilkarazapota , Antidesma bunius . Using a LC-MS/MS metabolomics workflow, it was previously reported that leaf extract fractions from these plant species contained characteristic phytochemicals (phenolics and flavonoids) that exhibited cytotoxic activities. …”
Section: Discussionmentioning
confidence: 99%
“…First, we created a database of all known and reported compounds found in select plant species that were reported to have cytotoxic activities: Mangifera indica, 23 Artocarpus heterophyllus, Annona muricata, 24 Lansium domesticum, 15 Manilkarazapota, 26 Antidesma bunius. Using a LC-MS/MS metabolomics 54 workflow, it was previously reported that leaf extract fractions from these plant species contained characteristic phytochemicals (phenolics and flavonoids) that exhibited cytotoxic activities. 23−26 Specifically, we examined the interactions of the top interacting compounds determined from our preliminary analyses and their plant sources: α-pinene (Mangifera indica), cyanomaclurin (Artocarpus heterophyllus), genistein (Annona muricata), kaempferol (Annona muricata and Antidesma bunius), norartocarpetin (Artocarpus heterophyllus), quercetin (Annona muricata, Antidesma bunius, Manilkara zapota, Manigfera indica), rutin (Annona muricata, Antidesma bunius, Lansium domesticum), and ellagic acid (Antidesma bunius, Mangifera indica) (Figures S1−S8).…”
Section: ■ Discussionmentioning
confidence: 99%
“…LC‐MS/MS analysis was carried out following our previous method. [ 7 ] Extracts were reconstituted in DMSO to make 1 mg/mL, which were then diluted to 125 μg/mL using 1:1 methanol‐water. These were then analysed using the Waters ACQUITY M‐Class Xevo G2‐XS QTof UPLC/MS system.…”
Section: Methodsmentioning
confidence: 99%
“…FBMN analysis was carried out following our previous method. [ 7 ] After acquiring mass spectrometry data, Waters raw files (.raw) were converted to abf files (.abf) using ABF converter and processed using MS‐DIAL. [ 8 ] Mass features ([M + H] + adducts) were identified using the following parameters: MS1 tolerance = 0.01 Da, MS2 tolerance = 0.025 Da, Maximum charge = 2, Mass range = 100‐1000, Minimum peak height = 10,000 counts.…”
Section: Methodsmentioning
confidence: 99%
“…The method is based on preparing solid media and adding a desired concentration of the extract to it. A certain volume of the extract can be mixed before the autoclaved medium is poured on Petri dishes or spread on their surface once it has solidified [ 71 , 76 , 117 ]. Subsequently, a small agar plug (4–7 mm in diameter) from an active fungal culture is inverted, with the mycelial surface facing down, and inoculated at the center of the agar plate.…”
Section: Biological Activity Of Plant Extracts and Essential Oilsmentioning
confidence: 99%